2023
DOI: 10.1126/science.adh0037
|View full text |Cite
|
Sign up to set email alerts
|

Histone removal in sperm protects paternal chromosomes from premature division at fertilization

Raphaëlle Dubruille,
Marion Herbette,
Maxime Revel
et al.

Abstract: The global replacement of histones with protamines in sperm chromatin is widespread in animals, including insects, but its actual function remains enigmatic. We show that in the Drosophila paternal effect mutant paternal loss ( pal ), sperm chromatin retains germline histones H3 and H4 genome wide without impairing sperm viability. However, after fertilization, pal sperm chromosomes are targeted by the egg chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…In the functional regard, protamines have recently gained a lot of attention. In the case of invertebrate protamines, the protamine-mediated removal of histones in the sperm of Drosophila (Rathke et al, 2014) has been shown to protect paternal chromosomes from premature division at fertilization (Dubruille et al, 2023). In mice, it has been shown that despite these protamines’ seemingly monotonous arginine composition, substituting a single lysine in protamine 1 in this vertebrate results in sperm chromatin and reproductive fitness alterations (Moritz et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In the functional regard, protamines have recently gained a lot of attention. In the case of invertebrate protamines, the protamine-mediated removal of histones in the sperm of Drosophila (Rathke et al, 2014) has been shown to protect paternal chromosomes from premature division at fertilization (Dubruille et al, 2023). In mice, it has been shown that despite these protamines’ seemingly monotonous arginine composition, substituting a single lysine in protamine 1 in this vertebrate results in sperm chromatin and reproductive fitness alterations (Moritz et al, 2023).…”
Section: Introductionmentioning
confidence: 99%